Power and anaerobic capacity in female soccer: A comparison between different age-categories - De Oliveira, F.; Neto, V. G. C.; Barbosa, R. J. S.; de Jesus, I. R. T.; da Silva Novaes, J.; Monteiro, E. R. (Apunts Sports Medicine, 2023)
Introduction Nowadays, female soccer can be considered one of fastest growing sports trends. However, investigations regarding female soccer players` performance are still scarce comparing to male soccer players. The purpose of this study was to compare the athletic profile of female soccer players from adult and youth categories of a professional soccer club.